Surface decoration with gH625-membranotropic peptides as a method to escape the endo-lysosomal compartment and reduce nanoparticle toxicity. (25th September 2015) - Guarnieri, D; Muscetti, O; Falanga, A; Fusco, S; Belli, V; Perillo, E; Battista, E; Panzetta, V; Galdiero, S; Netti, P A
Abstract: The membranotropic peptide gH625 is able to transport different cargos (i.e., liposomes, quantum dots, polymeric nanoparticles) within and across cells in a very efficient manner. However, a clear understanding of the detailed uptake mechanism remains elusive. In this work, we investigate the journey of gH625-functionalized polystyrene nanoparticles in mouse-brain endothelial cells from their interaction with the cell membrane to their intracellular final destination. The aim is to elucidate how gH625 affects the behavior of the nanoparticles and their cytotoxic effect. The results indicate that the mechanism of translocation of gH625 dictates the fate of the nanoparticles, with a relevant impact on the nanotoxicological profile of positively charged nanoparticles.